Comparison of physiological and biomechanical responses to flat and uphill cross-country sit-skiing in able-bodied athletes - Carlsen, C. H.; McGhie, D.; Baumgart, J. K.; Sandbakk, Ø. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To compare peak work rate (WRpeak) and associated physiological and biomechanical performance-determining variables between flat and uphill cross-country (XC) sit-skiing.